Bench press and pushup repetitions to failure with equated load - Eckel, T. L.; Watkins, C. M.; Archer, D. C.; Wong, M. A.; Arevalo, J. A.; Lin, A.; Coburn, J. W.; Galpin, A. J.; Brown, L. E. (International Journal of Sports Science & Coaching, 2017)
The bench press and pushup are commonly used for training upper body muscular strength and endurance. Although they are often used interchangeably, differences between the two relative to body mass load are unknown. Furthermore, sex differences may exist due to anthropometric body mass specificity. The purpose of this study was to evaluate the relationship between the pushup and bench press when performing repetitions to failure with an equated load. On day 1, 25 recreationally trained subjects (16 men, age=23.00±2.36 years, height=178.19±9.61 cm, mass=74.80±13.44 kg; 9 women, age=23.11±2.71 years, height=160.78±5.95 cm, mass=53.63±5.60 kg), performed a one repetition maximum bench press and an isometric pushup on a force plate to determine bodyweight load supported in both the up and down positions. Grip width on the bench press was measured as the distance between middle fingers and was used for hand placement during pushups. For the down position, a safety squat device was placed on the right triceps to signal that the upper arms were parallel to the ground, while for the up position, triceps were perpendicular to the floor. Days 2 and 3 consisted of performing repetitions to failure for either the bench press or pushup exercise with a load that was equal to the average relative bodyweight force of the up and down pushup positions. For the pushup, subjects followed a 60 beats per minute tempo and the test was terminated if they failed to complete a full repetition; they could not maintain cadence or there were three faults in form. For the bench press, they followed the same 60 s tempo and the test was terminated if they failed to complete a full repetition or could not maintain cadence. A 2 (exercise: bench press, pushup) x 2 (sex: men, women) mixed factor ANOVA demonstrated no interaction, but there were significant (P<0.05) main effects for exercise and sex where more repetitions were performed in the pushup (19.36±11.68 reps) than the bench press (11.40±8.38 reps) exercise. Also, men performed significantly more repetitions to failure (men=20.22±8.20 reps, women=6.78±5.69 reps). For combined sexes, there was a significant (P<0.05), strong relationship (r=0.82) between bench press and pushup repetitions to failure. For men, there was a significant (P<0.05), strong relationship (r=0.81), while for women, there was a moderate relationship (r=0.76). Men had significantly (P<0.05) greater bench press one repetition maximum (men=99.29±23.98 kg, women=42.17±8.88 kg), percentage of body mass supported as an average of the up and down positions (men=74.33±2.57%, women=69.70±2.63%) and bench press one repetition maximum relative to their body mass (men=1.32±0.22%, women=0.79±0.13%). The bench press and pushup are two distinct upper body exercises for repetitions to failure due to upper body musculature and body position sex differences. Choice of the pushup or bench press exercise should be based on training goal and sex. ABSTRACT FROM AUTHOR